The Promise – and Peril – of Web-Based Course Delivery in Adult and Continuing Education - Vivian W. Mott (Adult Education Research Conference, 2000)
Much has been argued about the advantages and pitfalls of computer technology in the delivery of adult education. This research examined the use of web-based instruction in terms of learner attitudes, students’ differential use of computer technology, and the impact on learning outcomes and technological competency.